2015
DOI: 10.1039/c5ra14518j
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable low temperature alcohol sensor based on hydrothermally grown tetragonal titania nanorods

Abstract: Highly stable, low temperature (27–175 °C) alcohol (ethanol, methanol and 2-propanol) sensing performance of a hydrothermally grown tetragonal TiO2nanorod array, targeting the detection level of 1–100 ppm, is reported in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
(97 reference statements)
1
25
1
Order By: Relevance
“…In contradiction with our observations, Moon et al presented that H 2 sensing of mesoporous titania was not effected by humidity variations (5%, 15%, 42%RH) at 140 • C [52]. Similarly, hydrothermally grown TiO 2 nanorods did not change the response values towards 1-100 ppm VOCs (ethanol, methanol, and propanol) at 75 • C under humidity variations (8%, 52%, 75%RH) [53]. The most probable reason for both of these cases is that the working temperatures were too low to initialize a strong chemisorption of water molecules on the surface of TiO 2 .…”
Section: Gas Sensingcontrasting
confidence: 99%
See 1 more Smart Citation
“…In contradiction with our observations, Moon et al presented that H 2 sensing of mesoporous titania was not effected by humidity variations (5%, 15%, 42%RH) at 140 • C [52]. Similarly, hydrothermally grown TiO 2 nanorods did not change the response values towards 1-100 ppm VOCs (ethanol, methanol, and propanol) at 75 • C under humidity variations (8%, 52%, 75%RH) [53]. The most probable reason for both of these cases is that the working temperatures were too low to initialize a strong chemisorption of water molecules on the surface of TiO 2 .…”
Section: Gas Sensingcontrasting
confidence: 99%
“…These are indicated in parentheses next to their response values in the table. Our rutile nanoporous titania sensor had better response values towards H 2 and C 2 H 6 O than similar nanoporous TiO 2 sensors [38,52,59], as well as most other nanostructures [53,[60][61][62]. Sensor response towards 25 ppm of C 2 H 3 N was 0.53 at 600 • C, which is an appropriate response value (≥0.1) to be used as an early detection system for acetonitrile exposure.…”
Section: Gas Sensingmentioning
confidence: 75%
“…Thus, this justifies the behavior we noticed in our TNW-based sensor. Several studies , have also observed the same behavior using TiO 2 -based sensors. Furthermore, in Figure S9, the shorter response and recovery times observed for the TNW sensor tested in C 7 H 8 vapor in the presence of RH in comparison to that in dry air clearly prove the existence of a catalytic influence for our sensor.…”
Section: Resultssupporting
confidence: 58%
“…nanosheets and three-dimensional (3D) e.g. nanoflower for different applications [11,13]. The nanoparticles (OD) have attracted the great attention of researchers in the gas sensing fields.…”
Section: Introductionmentioning
confidence: 99%